Polyphosphate-enhanced production of reactive oxidants by nanoparticulate zero-valent iron and ferrous ion in the presence of oxygen: Yield and nature of oxidants - Kim, Hak-Hyeon; Lee, Hongshin; Kim, Hyung-Eun; Seo, Jiwon; Hong, Seok Won; Lee, Jeong-Yong; Lee, Changha (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The production of reactive oxidants from nanoparticulate zero-valent iron (nZVI) and ferrous ion (Fe(ll)) in the presence of oxygen was greatly enhanced by the addition of tetrapolyphosphate (TPP) as an ironchelating agent. Compared to other ligands, TPP exhibited superior activity in improving the oxidant yields. The nZVI/TPP/O-2 and the Fe(II)/TPP/O-2 systems showed similar oxidant yields with respect to the iron consumed, indicating that nZVI only serves as a source of Fe(II). The degradation efficacies of selected organic compounds were also similar in the two systems. It appeared that both hydroxyl radical (13H) and ferryl ion (Fe(IV)) are produced, and "OH dominates at acidic pH. However, at pH > 6, little occurrence of hydroxylated oxidation products suggests that Fe(IV) is a dominant oxidant. The degradation rates of selected organic compounds by the Fe(II)/TPP/O-2 system had two optimum points at pH 6 and 9, and these pH-dependent trends are likely attributed to the speciation of Fe(IV) with different reactivities. (c) 2015 Elsevier Ltd. All rights reserved.